Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan pada Usaha Zeeice Jeruk Peras di Sidoarjo - Aidah, Heni Nur; Boyas, Jeziano; Qurratu'aini, Nafia; P, Devika Cherly (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this research is to examine how Zeaice pay and work disciplinary policies affect productivity on the job. This study employs a quantitative technique. Saturated sampling was utilised to gather responses from all 35 employees of Zeaice. A questionnaire evaluating variables using a Likert scale was used to gather data. Contrary to popular belief, the study found that work discipline significantly affects employee performance, but compensation had no such influence. Pay and workplace discipline both influence productivity at the same time.